Evaluation of the Relationship Between Capital Budget and Financing Decisions in Firm Growth - Amin, Amelia Rezki Septiani; Adil, Muhammad (Economics and Digital Business Review, 2025)
Purpose: This study evaluates the intricate relationship between capital budgeting, financing decisions, and firm growth, emphasizing how these financial strategies collectively influence corporate expansion, financial stability, and competitive advantage. The study comprehensively assesses how firms optimize capital allocation and funding decisions to sustain long-term growth by integrating findings from diverse economic and industrial contexts. This research employs a Systematic Literature Review (SLR) approach to synthesize and critically analyze existing studies on capital budgeting, financing decisions, and their implications for firm growth. The study reviews peer-reviewed literature from recognized academic sources, examining theoretical frameworks, empirical findings, and emerging trends in corporate financial decision-making. The analysis focuses on key financial models, including Trade-Off Theory and Pecking Order Theory, to contextualize findings and highlight inconsistencies across existing studies. The study finds that an integrated approach to capital budgeting and financing decisions significantly impacts a firm's ability to strategically allocate resources, balance debt and equity, and mitigate financial risks. Firms that effectively leverage NPV, IRR, and Payback Period methods exhibit greater investment efficiency, while those with over-reliance on debt face risks of over-leverage and financial distress—external factors such as interest rates, inflation, and regulatory changes shape firms' financial strategies. The study offers practical insights for corporate managers to develop flexible and adaptive financial strategies, ensuring sustainable corporate growth. Policymakers can leverage these findings to refine financial regulations, fostering an investment-friendly environment. Future research should explore ESG financing, fintech-driven financial solutions, and cross-industry capital allocation models to expand current knowledge.